Utilization Of State Property By Partners In The Perspective Of Utilitarianism Legal Theory - Sri Hartati; Dani Sintara; Halimatul Maryani (Veteran Law Review, 2022)
The problem of the utilization of   state property, needs to be studied after the Regulation of the Minister of Finance No. 115 / PMK.06 / 2020 on the Utilization of   state property. Utilization of   state property in practice, some are done by partners, such as what is the right to ownership of state assets and also the results of empowered utilization to increase state assets need to be analyzed in the perspective of utilitarianism legal theory. The research method used is normative juridical. The results showed that the utilization of   state property by partners cannot be transitioned into property rights and must also be utilized productively to increase state assets.  The right of utilization of   state property is  not essentially a property, so when using state assets,   state property can only be used for productive assets, with the result of providing benefits to increase state assets. As a result, state assets are non-transferable when using   state property.